(untitled) (REVISTA NODO, 2015)
In the context of higher education in Colombia, the recognition of certain equivalence between scientific research and artistic creation has achieved official recognition. However, at the high studies level the subject area of “Engineering, Architecture, Urban and others” urban artistic practices are still not significant form of knowledge production and research. This article argues that artistic practices represent a particularly suggestive research field for the study of “restless places” in the contemporary city: limited spaces generated by the effects of globalization, “living” places rather than lived places, which usually generate creative and collaborative processes of habitat construction.